Interpretation Of Dreams - Ibn Raashid Al-Bakri Al-Qafsi; + (Lahore Darussalam, 2010)
The Present book tackles the issue of the interpretation of dreams in the light of the Quran and the Sunnah, based on the Prophet's hadeeth in which he said, "The dream of a Muslim is one of the forty-six parts of prophethood. " In this book, the author provides a definition of the word 'dream', discusses the various types of dreams, mention some dreams that were interpreted by the Prophet PBUH etiquette to be observed by the person who has a dream and the person who has a dream and the person who interprets it and provides the interpretation of a large number of dreams, among some other issues related to the subject. The author is the well-known erudite scholar Sheikh Muhammad ibn Abd-Allah ibn Raashid al-Bakri (d. 736 Ah/1336 CE). The english reader will defenitely find this book highly interesting and thought-provoking.
Includes Citations.
Keywords: Dreams -- Early works to 1800